Business start-up and growth motives of entrepreneurs: A case in Bradford, United Kingdom - L. Ranmuthumalie De Silva (The University of Manchester, Manchester Business School, 2010)
This study attempts to investigate start-up and growth motives of entrepreneurs who own small and medium scale enterprises in Bradford, UK. In-depth interviews are conducted using storytelling approach and narrative analysis is used for data analysis. The Findings reveal that each entrepreneur is motivated by a combination of pull and push motives at the start-up stage while they are mainly motivated by pull motives at the growth stage. Based on patterns observed between growth motives and entrepreneurial outcomes, three types of entrepreneurs are identified. Practical implications and avenues for future research are highlighted.
Keywords: 330